Antiangiogenic Effects of VH02, a Novel Urea Derivative: In Vitro and in Vivo Studies - Suwadee Phowichit; Miho Kobayashi; Yuriko Fujinoya; Yasufumi Sato; Kingkarn Sanphanya; Opa Vajragupta; Linda Chularojmontri; Suvara K. Wattanapitayakul (Molecules, 2016)
Vascular endothelial growth factor receptor 2 (VEGFR2) is a vital target for therapeutic intervention in cancer. We have recently described a computer-based drug design for a small molecule VEGFR2 inhibitor named VH02 (1-((1-(1H-indazol-6-yl)-1H-1,2,3-triazol-4-yl)methyl)-3-(3-chloromethylphenyl)urea). This study aimed to further explore the anti-angiogenic activity of VH02 both in vitro and in vivo. The in vitro assays include cell viability, capillary-like tube formation, MMP activity, and western blot analyses of signaling through VEGFR2 while the in vivo anti-angiogenic response were performed to evaluate the effect on vascularization in Matrigel plug applied in C57BL/6L mice. VH02 reduced angiogenesis behavior of EA.hy926 including cell viability, migration, adhesion, capillary-like tube formation, and MMP-2 activity induced by VEGF. Furthermore, VH02 regulated angiogenesis by directly inhibiting VEGFR2 on Tyr1175 signaling pathway leading to the inhibition of Akt-mediated cell survival and migration. Disruption of phosphorylation at VEGFR2-Tyr1175 by VH02 abolished FAK-Tyr397 signaling but not phosphorylation of p38 MAPK. This suggests that blockade of FAK by VH02 apparently associated with reduction of endothelial cell motility. Actin cytoskeleton rearrangement was diminished by VH02 in human endothelial cells. The anti-angiogenic effect of VH02 was confirmed in the in vivo model, revealing the reduction of vascular density in Matrigel plug after VH02 treatment. Additionally, the pericyte-like cells surrounding blood vessels in the plugs were significantly reduced as well as vascular density and p-Akt intensity. Our findings indicate that VH02 successfully inhibits VEGF-induced angiogenesis both in vitro and in vivo models. The compound could be further developed as an antiangiogenesis agent for cancer therapy.